Integration of design for manufacturing and assembly (DfMA) and theory of inventive problem solving (TRIZ) for design improvement - Wan Abu Seman, Sharifah Zainaf (2010)
The quality of the product mostly depends on element such as product design, material used, function, assembly time and manufacturing cost. So a systematic method procedure needs to achieve the target need. Methods to be developed are with the help of TRIZ (the Russian abbreviation of the theory of inventive problem solving) and DFMA (design for manufacturing assembly approach). These methods focus on innovation within the whole function and mechanism structure of the base product. The approach methods been used based on criteria in each method and all the criteria will be analysed during product design stage. During the stage of design, a significant amount of information is gathered and analyzed to support the decision making process that leads to the synthesis of products. This approach first reveals the contradictions that block the target quality from being reached, based on the engineering solutions that the current base product employs and the phenomena that take place while the base product is performing its function. This will make product more competitive and effective with good quality and at the same time reduce the conflict faces.